Skills for a Modern Ukraine - Del Carpio, Ximena (Washington, DC: World Bank, 2016)
Ukraine’s economic progress since its independence in the early 1990s has been uneven, in part due to the slow pace of reforms, unfavorable demographic factors, and low productivity. One of the key factors limiting success is the inadequacy of the skills of Ukraine’s workforce with the needs of a modern economy. While the country demonstrates a strong record of educational attainment and acquisition of foundational skills, the post-secondary education and training system fails to equip workers with the right advanced skills for labor market success. This study provides new evidence on the nature of skills valued in the labor market, reviews the institutional constraints hindering the development and use of workforce’s skills, and proposes a set of policy options.